Treatment of infrapopliteal post-PTA dissection with tack implants: 12-month results from the TOBA-BTK study - Brodmann, Marianne; Wissgott, Christian; Holden, Andrew; Staffa, Robert; Zeller, Thomas; Vasudevan, Thodur; Schneider, Peter (Catheterization and cardiovascular interventions, 2018)
OBJECTIVES: The Tack implant is designed for focal, minimal metal management of dissections. This study evaluated Tacks for treating postpercutaneous transluminal angioplasty (PTA) dissection in patients with below-the-knee (BTK) arterial occlusive disease. BACKGROUND: PTA is the most commonly used endovascular treatment for patients with occlusive disease of the BTK vessels. Post-PTA dissection is a significant clinical problem that results in poor outcomes, but currently there are limited treatment options for managing dissections. METHODS: This prospective, single-arm study evaluated patients with CLI and BTK lesions; 11.4% were Rutherford category (RC) 4 and 88.6% were RC 5. BTK occlusive disease was treated with standard PTA and post-PTA dissections were treated with Tack placement. The primary safety endpoint was a composite of major adverse limb events (MALE) and perioperative death (POD) at 30 days. Other endpoints included: device success; procedure success (vessel patency in the absence of MALE); freedom from clinically driven target lesion revascularization (CD-TLR); primary patency; and changes in RC. Data through 12 months are presented. RESULTS: Thirty-two of 35 (91.4%) patients had post-PTA dissection and successful deployment of Tacks. Procedural success was achieved in 34/35 (97.1%) patients with no MALEs at 30 days. The 12-month patency rate was 78.4% by vessel, 77.4% by patient, and freedom from CD-TLR was 93.5%. Significant (P < .0001) improvement from baseline was observed in RC (75% of patients improved 4 or 5 steps). CONCLUSION: Tack implant treatment of post-PTA dissection was safe and effective for treatment of BTK dissections and resulted in reasonable 12-month patency and low rates of CD-TLR.
Keywords: balónková angioplastika; senioři; průchodnost cév; Prosthesis Design; senioři nad 80 let; tibial artery; Europe; Time Factors; doba přežití bez progrese choroby; Self Expandable Metallic Stents; Evropa; Nový Zéland; Ischemia; mužské pohlaví; Vascular Patency; infrapopliteal arteries; Prospective Studies; poranění cév; protézy - design; ischemie; onemocnění periferních arterií; Angioplasty, Balloon; Aged, 80 and over; dissection; New Zealand; ženské pohlaví; critical limb ischemia; Humans; prospektivní studie; kritický stav; balloon angioplasty; Progression-Free Survival; časové faktory; endovaskulární výkony; Endovascular Procedures; samoexpandibilní metalické stenty; Peripheral Arterial Disease; rizikové faktory; peripheral artery disease; slitiny; Leg; Alloys; Vascular System Injuries; bérec; Female; Aged; Risk Factors; Critical Illness; lidé; Male